PENGARUH BIMBINGAN UJI KOMPETENSI ONLINE TERHADAP HASIL TRY OUT LOKAL UJI KOMPETENSI MAHASISWA AKPER RS. DUSTIRA - Novi Malisa (Jurnal Skolastik Keperawatan, 2020)
Competency Test aims to achieve a standard graduate competency that meets working standards as healthcare personnel. Therefore, the graduation of competency test is very important for the health workers to be able to gain recognition for their competence. Various methods have been applied by educational institutions to prepare their students for the competency test. The purpose of this research is to know the influence of the guidance of online competency Test against the results of the local try-out student Competency Test Akper RS. Dustira. Design research using one group pre-post test design. The population in this study is a level III student of Akper RS. Dustira. A research sample of 125 respondents was taken with the Purposive Sampling technique. Data obtained through the local try-out activity of the competency test with the number of questions 180 vignette questions that have been compiled by a team that has certificate development and item review items with an online system. Data analysis Using test paired t test with α = 0.05. The results showed that the average pre test value before the intervention was given was 46.9110 with 38.4% of the respondents could not meet the pass limit. Average post test value after given intervention is 80.2845 with 100% of respondents can meet the pass limit. Online tutoring proved to significantly increase the value of students when the try out local competency test (P = 0,000). Online guidance can be used as an alternative program method to prepare students for competency test.